Hydrogen Production by Supercritical Water Gasification of Biomass - Kipcak, Ekin; Akgun, Mesut (SPRINGER, 2015)
It is widely accepted that hydrogen energy can sustainably provide the world's growing energy needs. Currently, hydrogen is produced from mainly nonrenewable feedstocks through biochemical and thermochemical technologies. However, to achieve a genuinely sustainable, economic, viable, and environmentally benign technology, hydrogen will need to be produced from renewable energy sources through innovative production processes. This chapter focuses on one of these technologies that provide a novel approach for hydrogen production: supercritical water gasification of biomass. The process has significant potential for the conversion of biomass to produce hydrogen and other combustible gases. It also has major advantages when compared with other processes, such as eliminating the necessity for drying of the feedstock, providing high gasification efficiency and hydrogen selectivity, enabling the formation of clean gaseous products, and producing much lower amounts of tars and chars. To increase the hydrogen selectivity, the use of catalysts is common, with the preferred catalysts being alkaline salts, some metals, and metal oxides. The supercritical water gasification process can exhibit different gas compositions or activities with respect to the feedstock, reaction conditions, or catalyst used. Therefore, in this chapter, hydrogen production from various biomass sources by supercritical water gasification is comparatively discussed with examples from the literature. The term biomass covered in this chapter includes model compounds (such as glucose, cellulose, and lignin), alcohols, and real biomass (such as industrial wastewaters and sewage sludge). The effects of reaction time, system temperature and pressure, biomass concentration, oxidant concentration, catalyst use, and the kind of catalyst on the hydrogen yield are investigated.
Keywords: Biofuel; Biomass; Catalyst; Hydrogen; Supercritical water; Supercritical water gasification; PARTIAL OXIDATIVE GASIFICATION; HOT COMPRESSED WATER; MILL WASTE-WATER; HYDROTHERMAL GASIFICATION; CATALYTIC GASIFICATION; SEWAGE-SLUDGE; MODEL COMPOUNDS; LIGNIN GASIFICATION; METAL-CATALYSTS; WOODY BIOMASS; Biotechnology & Applied Microbiology; Energy & Fuels; Engineering